Artificial noise-aided robust secure information and power transmission scheme in heterogeneous networks with simultaneous wireless information and power transfer - Bo ZHANG; Kaizhi HUANG; Zhou ZHONG; Yajun CHEN (Tongxin xuebao)
A heterogeneous network with simultaneous wireless information and power transfer under the stochastic channel state information (CSI) error was considered.In this network,to guarantee the security and reliability of information and energy transmission,an artificial noise (AN)-aided robust secure information and power transmission scheme was proposed.By jointly designing the downlink information beamforming and AN matrix of macrocell base station and femtocell base stations,the eavesdroppers were jammed and the energy receiving performance of system was improved simultaneously.The problem of maximizing the energy receiving performance was modeled under the constraints on the base station power,the outage probability of information transfer and confidential information eavesdropped.Due to the probabilistic and rank-one constraints,this problem was non-convex.To obtain the solution,the original problem was first transformed into an equivalent form,which was easy to process.Then,the Bernstein-type inequality and the Large-deviation inequality was utilized to transform the outage probability limits into convex linear matrix inequalities,respectively.Finally,the rank-one beamforming constraints were processed with quadratic equality constraint procedure.Simulation results show that the proposed scheme has higher energy receiving performance and feasible performance in comparison with compared schemes,which validates the effectiveness and the robustness of our proposed scheme.